Static isotropic pressure induced ultra-wide band gap response of NaCaF3 fluoro-perovskite and its repercussions on optical properties: ab initio calculation. Issue 18 (12th December 2021) - Gillani, S. S. A.; Fatima, Nisar; Zeba, I.; Shakil, M.; Kiran, R.; Tahir, M. B.; Rizwan, Muhammad; Ahmad, Riaz; Jawad, A.
ABSTRACT: A comprehensive theoretical study to investigate the outcomes of externally applied static isotropic pressure (0–50 GPa) on electronic, optical and structural properties of NaCaF3, using density functional theory based CASTEP code with ultra-soft pseudo-potential USP plane wave and Perdew Burke Ernzerhof exchange–correlation functional of Generalized Gradient Approximation, is reported. The electronic band gap shows the increasing trend 4.773–6.203 eV with increasing external pressure. The increase in band gap is significant up to 20 GPa as compared to higher external pressures. The mystery of increasing band gap is nicely decoded by the total density of states and elemental partial density of states. Optical properties have been calculated to analyse the impact of increment in band gap on them. We observed that the highest peak of energy loss function L ( ω ) shows the blue shift which confirms the increment of band gap. At zero photon energy, for 0 GPa, the static refractive index n ( ω ) has a value of 1.4456. After applying external pressure, there is a slight increase in n ( ω ) which favours the ultrawide band gap behaviour of the ternary compound. The energy points at which the absorption peak is maxima, the refractive index has lowest value.